Peran Media Sosial Dalam Dinamika Opini Publik dan Partisipasi Politik Era Digital - Juleha Juleha; Jusfira Yuniar; Nur Riswandi Marsuki (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The emergence and development of information technology is changing people's behavior. These changes occur in human thought patterns, feelings and actions. Social media can clearly be used by the government to guide public opinion and influence political participation. In a democratic country like Indonesia, public opinion is very important because the government cannot function without public opinion. Therefore, the author is interested in conducting research on the role of social media in the dynamics of public opinion and political participation in the digital era. The method in this article uses library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. The data collection technique used was internet searching and documentation studies were used. In writing this scientific work, the first data analysis technique is data reduction, which means that the analysis is carried out to summarize the data, the researcher selects data that is really important to include in this scientific work and displays the data (data presentation). The research results found that in the current digital era, social media plays an important role in political participation and public opinion. Changes in the way people communicate, obtain information, and engage in politics are some examples. Social media influences public opinion and political participation. effects, both positive and negative. Of course, the government must monitor political activities amidst the development of social media in the modern era.